Hiperbilirrubinemia como predictor de perforación apendicular en pacientes del servicio de emergencia del Hospital Manuel Ygnacio Monteros de Loja. - Vicente Rivas, Alexander Fabricio (2016)
The perforated appendicitis (AP) presents a late intervention in 5 and 30%, leading to an increase in mortality of 0.3% in acute appendicitis and 6.5% in the case of a perforated appendix, an adequate surgical approach would help to reduce mortality, stay In-patient secondary to peritonitis, sepsis of abdominal origin, abscesses, etc. For this it is important to emphasize a better prognostic, actually studies reporting that hyperbilirubinemia produced by hepatocellular damage and intrahepatic cholestasis as the result of decreased portal blood flow are reported to be a predictive factor for AP. The aim of the present study was to determine serum levels of total bilirubin in the relation to surgical and histopathological findings, to characterize, postoperative and preoperative cases, and to determine if hyperbilirubinemia is a predictor of appendicular perforation by evaluating its sensitivity, specificity, positive predictive value (VPP) and negative predictive value (VPN). This retrospective study of 107 cases treated in emergency with total bilirubin values as part of their preoperative assessment was presented and who underwent appendectomy in the Manuel Ygnacio Monteros Hospital of Loja (HMYM). It has been made the review of clinical histories, bilirubin value, surgical and histopathological findings, sensitivity, formulas of sensitivity, specificity, VPP, and NPV were used according to the Bayes' theorem; As a result 62% of patients with total bilirubin < 1.10 mg / dl were found, of which 7% had AP; While 38% with hyperbilirubinemia and 17% presented AP. It is concluded that hyperbilirubinemia is presented with higher percentage in AP. Keywords: Perforated apendicitis - Hyperbilirubinemia